Neutron scattering studies of the methanol-to-hydrocarbons reaction. Issue 7 (16th March 2023) - Zachariou, Andrea; Hawkins, Alexander P.; Collier, Paul; Howe, Russell F.; Parker, Stewart F.; Lennon, David
Abstract : The application of neutron scattering techniques (inelastic neutron scattering, quasi-elastic neutron scattering and neutron diffraction) to explore concepts connected with the methanol-to-hydrocarbon reaction over the zeolite ZSM-5 are considered. Reproduced from [ Cat. Sci. Tech., 2018, 8, 3304–3312] under a Creative Commons Attribution Licence (CC-BY). Abstract : The methanol-to-hydrocarbons reaction uses a zeolite catalyst (typically H-ZSM-5 or SAPO-34) to produce light olefins (mainly C2 –C4 ) for chemical feedstocks and methylated benzenes for use as fuels. The reaction is a major industrial process world-wide, and consequently it has been extensively studied by a wide range of physical methods ( e.g. reaction testing) and spectroscopic methods. One approach that has been used relatively little to-date is neutron scattering. Neutron methods can provide information about structure, diffusion at the microscopic scale and vibrational spectra that are not limited by selection rules, fluorescence or absorption. In this mini-review we give a short introduction to neutron scattering, then describe how neutron scattering provides insight into the Brønsted acid sites of the catalyst, then consider each of the three stages of the process; induction, steady-state and deactivation. We conclude with a perspective on how neutron scattering can further support studies of MTH chemistry.